2007
DOI: 10.1016/j.pain.2007.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intra-oral pain on motor cortex neuroplasticity associated with short-term novel tongue-protrusion training in humans

Abstract: To determine if short-term (15 min) training in a novel tongue-task is associated with rapid neuroplasticity of the tongue primary motor area (MI) in the human cerebral cortex, and if intra-oral tonic pain affects the tongue MI neuroplasticity and tongue-task training performance. Nine healthy volunteers (7 men, 2 women, mean age 24+/-1.1 years) participated in two cross-over training sessions in which the application to the tongue of the algesic chemical capsaicin (1%) or vehicle cream was randomized. Prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
160
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(183 citation statements)
references
References 72 publications
18
160
2
3
Order By: Relevance
“…Earlier research regarding hand and leg rehabilitation using motor training with sensory stimulation suggested that that this type of combined stimuli can induce larger changes in excitability and/or neuroplasticity in motor cortex [39][40][41] , whereas tongue protrusion motor training, which alone produces measured neuroplasticity and successful performance, was less effective on motor cortex with nociceptive sensory stimulation. 42 These may be due to the differences in the neural systems between spinal and cranial nerves or in the type of experimental noxious stimulus. It seems reasonable to infer that swallowing motor movement innervated by cranial (vagus and glossopharyngeal) nerves, as with the tongue training, may block or reduce the long-term effect of PES as discussed above.…”
Section: Changes In the Corticobulbar Neural Circuitmentioning
confidence: 99%
“…Earlier research regarding hand and leg rehabilitation using motor training with sensory stimulation suggested that that this type of combined stimuli can induce larger changes in excitability and/or neuroplasticity in motor cortex [39][40][41] , whereas tongue protrusion motor training, which alone produces measured neuroplasticity and successful performance, was less effective on motor cortex with nociceptive sensory stimulation. 42 These may be due to the differences in the neural systems between spinal and cranial nerves or in the type of experimental noxious stimulus. It seems reasonable to infer that swallowing motor movement innervated by cranial (vagus and glossopharyngeal) nerves, as with the tongue training, may block or reduce the long-term effect of PES as discussed above.…”
Section: Changes In the Corticobulbar Neural Circuitmentioning
confidence: 99%
“…There is striking evidence supporting this view from a recent study in healthy individuals showing that acute pain can prevent motor-cortex plasticity associated with novel motor training and impair the ability to learn a new motor task. 36 In this study, healthy volunteers participated in two crossover training sessions in which they were trained in a tongue-protrusion task. Prior to each training session, a cream was applied to the tongue that contained either capsaicin (inducing moderate intra-oral tonic pain) or an inert substance (control condition).…”
Section: Does Acute Pain Interfere With Motor-cortex Activity?mentioning
confidence: 99%
“…Changes in motor representations may also occur in that part of face-M1 representing the tongue following the training of humans and monkeys in a novel tongueprotrusion task (Boudreau et al, 2007;Sessle et al, 2007;Svensson et al, 2006). Although these studies suggest that face-M1 has the capacity to undergo neuroplastic changes and be remodelled throughout life, very few studies have tested for possible neuroplastic changes within face-M1 following intraoral manipulations Sessle et al, 2005Sessle et al, , 2007, and no study has addressed whether loss of teeth induces neuroplastic changes in the ICMS-defined features of face-M1, despite tooth extraction or loss of teeth for other reasons (e.g., trauma) being a common occurrence in humans and animals that may be associated with changes in sensorimotor behaviors (Endo et al, 1998;Hannam et al, 1977;Miehe et al, 1999).…”
mentioning
confidence: 99%